2015
DOI: 10.2147/ndt.s73333
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse cerebral vasospasm after resection of schwannoma: a case report

Abstract: BackgroundThe etiology of vasospasm after brain tumor resection remains unclear. This is the first report of diffuse cerebral vasospasm following resection of a schwannoma located in the left portion/part of the ventral medulla oblongata.Case presentationA 16-year-old boy presented with dizziness and projectile vomiting without apparent cause three months before admission. Magnetic resonance imaging revealed a space-occupying lesion in the left portion of the ventral medulla oblongata. The tumor was completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Most patients with cerebral vasospasm after posterior fossa schwannoma excision were young, with 4 of 5 being younger than 40 years of age. 3 , 5 , 7 , 8 However, as in our case, 1 patient with vestibular schwannoma excision was 69 years old, and the author also described the tumor as having a cystic component. 6 Two cases were reported to have undergone a cerebrospinal fluid (CSF) diversion procedure before the tumor excision, and in 1 of the cases, the authors suggested a relative paucity of CSF in the cisterns as a predisposing factor for vasospasm.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Most patients with cerebral vasospasm after posterior fossa schwannoma excision were young, with 4 of 5 being younger than 40 years of age. 3 , 5 , 7 , 8 However, as in our case, 1 patient with vestibular schwannoma excision was 69 years old, and the author also described the tumor as having a cystic component. 6 Two cases were reported to have undergone a cerebrospinal fluid (CSF) diversion procedure before the tumor excision, and in 1 of the cases, the authors suggested a relative paucity of CSF in the cisterns as a predisposing factor for vasospasm.…”
Section: Discussionsupporting
confidence: 56%
“… 11 The direct mechanical trauma to the arterial wall during tumor resection can induce local artery vasoconstriction, which results in an intrinsic myogenic response, upregulated norepinephrine levels, or increased cerebrovascular reactivity to norepinephrine and serotonin. 8 Young people have enhanced contractility and elasticity of their arterioles, which can make them more susceptible to direct mechanical stress. In fact, the incidence of symptomatic vasospasm is lower among patients with aSAH who are older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior fossa tumors accounted for relatively less symptomatic vasospasm in comparison with anterior/middle fossa lesions after operation[ 7 , 20 ]. However, nearly all types of tumor in the posterior fossa can be encountered to be associated with cerebral vasospasm[ 3 , 21 24 ]. Moreover, it was revealed that more than half of patients with acoustic neurinomas presented anterior circulation vasospasm postoperatively[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common predisposing factor for vasospasm onset following intracranial tumor resection is SAH ( 4 ). Blood accumulation in the basal cisterns is thought to be an important factor in initiating the vasospasm ( 5 ).…”
Section: Introductionmentioning
confidence: 99%